Regional anthropogenic disturbance and species-specific niche traits influence the invasiveness of European beetle species - Simões, Marianna V. P.; Nuñez-Penichet, Claudia; Warren, Dan; Schmitt, Thomas; Krull, Marcos (Frontiers in Ecology and Evolution, 2023)
Coleoptera are key elements of terrestrial trophic interactions and generate significant economic and aesthetic ecological benefits, but their representatives also represent severe pest species. Understanding how invasive species operate is indispensable to identify and anticipate potential invasion areas. However, few studies have explored niche dynamics and drivers of invasions in this group. Here we examined niche dynamics across 54 invasive beetle species native to Europe and assessed whether factors such as human influence index, feeding habits, body size, and niche breadth are associated with the degree of invasion. The realized niches had low similarity in invasive and native ranges (i.e., invaded areas are climatically dissimilar to native ranges). This included a high degree of niche expansion in invaded areas but also environments occupied in the native ranges but unoccupied in the invasive range (unfilling), suggesting that altered species–climate relationships during invasion processes are common. Niche expansions showed positive association with small native niche breadth sizes and movements from highly disturbed native areas to less disturbed invaded ranges; unfilling was associated with invaded niche breadth size and frequency of species occurrence. Both were related to dissimilar realized climatic niches in invaded ranges. Colonization of invaded areas might be triggered by low quality resources in native areas. Unfilling levels might be related to the year of introduction and loss of biotic constraints present in their native distribution, leading to the use of different climatic spaces in the invasive areas. This idea is reinforced by larger invasive climatic niche breadth. Our results provide insight into patterns of invasive species, and initial holistic exploration towards the understanding of invasive species dynamics.